2019
DOI: 10.1089/vim.2019.0058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus Genotypes in Pakistan: Current Scenario and Review of Literature

Abstract: Hepatitis C virus (HCV) is a major public health concern globally, resulting in liver-related complications. Approximately 6% population of Pakistan is infected with HCV. HCV is error prone, due to which it is classified into 7 genotypes and 67 subtypes. HCV genotype determination is critical for treatment and therapy response. In this study, 3,539 samples were collected from 2015 to 2019 from all over Punjab. RNA was extracted from samples using QIA Amp Viral RNA MINI kit (Qiagen, Germany) and viral genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 69 publications
3
46
0
Order By: Relevance
“…The results of the current study showed that HCV genotype 3a is the most prevalent viral genotype in the studied population. Similarly, previous studies from other cities of Punjab, Pakistan showed that 3a is the most frequent genotype [18]. In the current study, 3a was found to be the most common in age group 26-55 with the prevalence rate of 68.72%, followed by genotype 1 with 5.24% prevalence rate.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of the current study showed that HCV genotype 3a is the most prevalent viral genotype in the studied population. Similarly, previous studies from other cities of Punjab, Pakistan showed that 3a is the most frequent genotype [18]. In the current study, 3a was found to be the most common in age group 26-55 with the prevalence rate of 68.72%, followed by genotype 1 with 5.24% prevalence rate.…”
Section: Discussionsupporting
confidence: 83%
“…In 2018, out of a total of 59 HCV serum samples 23 (38.9%) were collected from males and 36 (61%) were collected from females. In 2019, out of 100 infected patients 40 (40%) were male and 60 (60%) were female [18]. In the current report, 3a was found to be the most prevalent genotype in Punjab followed by untypable genotypes and genotype 1a, respectively.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In Pakistan, an estimated of around 9.4 million people (about 5.4% of the population) are infected by HCV (3,20,25,24). The immune-based therapy for viral elimination is effective in about 50% cases of genotype 1, 4, 5, and 6 and about 80% cases of genotype 2 and 3 (43,46,48,54), but still viral relapse is very frequent (55,56) and the therapy itself has serious side effects that range from flu-like symptoms to thrombocytopenia and suicidal tendencies (7,12,27,33).…”
Section: Introductionmentioning
confidence: 99%
“…Every year, 1.4 million people die due to viral hepatitis, of whom 90% of deaths are due to hepatitis B or C [3,4]. Pakistan is bearing 2nd highest burden of global hepatitis C prevalence with 7.44% population carrying HCV [5]. Around 1.98% of the Pakistani population is having HBV antigen in their blood [6].…”
Section: Introductionmentioning
confidence: 99%